A efetividade do trabalho técnico social no empreendimento do MCMV/FAR em Itabuna(BA): caso da apropriação socioterritorial dos moradores do Vida Nova - Marques, Carlos Alberto Bispo (2019)
This dissertation proposed to evaluate the Social Technical Work Effectiveness (TTS) of the Minha Casa Minha Vida Program financed through the Residential Leasing Fund (MCMV / FAR) in the municipality of Itabuna(BA), based on the experience of the socio-territorial appropriation of the Housing Vida Nova. It was intended for an evaluation of the TTS carried out with the residents of this project in order to know if after its execution occurred significant changes characterized as socio-territorial appropriation in the reality of these residents; and thus to recognize the effectiveness or not of the TTS thought as complementary component of the policy of Housing of Social Interest (HIS).The study showed that the TTS presents itself, historically, through aspects that the reissue now, and innovates it in the context of the HIS policy in the country in face of the political, ideological and institutional contours that occurred in each time considered in this investigation. In Itabuna, the adhesion to the MCMV / FAR was carried out in 2009 and among the commitments signed with Mcidades, the responsibility of the local public entity for the execution of the TTS in the projects built in the city was highlighted. This research was guided by a theoretical, technical and conceptual discussion of the TTS to recognize the multiple social determinations that guided the subject in question. Bibliographical, documentary and field surveys were carried out; the latter, with a semi-structured interview with residents of the Vida Nova project. The results indicated that the effectiveness of TTS, in the light of the perceptions of the residents of Vida Nova, was fragile and fragmented. This is explained when the aspects of autonomy, protagonism and social participation of these residents as elements that characterize the socio-territorial appropriation necessary to ensure the right to the city were evaluated.